RNA-SEQ: A GLANCE AT TECHNOLOGIES AND METHODOLOGIES (2015)
RNA Sequencing (RNA-Seq) is a newly born tool that has revolutionized the post-genomic era. The data produced by RNA-Seq, sequencing technologies and use of bioinformatics are exploding rapidly. In recent years, RNA-Seq has been the method of choice for profiling dynamic transcriptome taking advantage of high throughput sequencing technologies. RNA-Seq studies have shown the transcriptome magnitude, notion and complexity. From 2008, as its introduction year, the relevant reports on RNA-Seq have been multiplied by more than 2822 times just in 6 years. RNA-Seq also contributes a more accurate gene expression and transcript isoform estimation than other methods. Furthermore, some of the potential applications for RNA-Seq cannot be conducted by other methods and as yet are unique to RNA-Seq. As RNA-Seq approaches increase in speed and decrease in cost, more distinct researches are applied and become more common and accurate. RNA-Seq is a cross and interdisciplinary method that interconnects biology to other scientific topics. This article describes RNA-Seq approach, technologies, methodologies, implementation and methods done so far in characterizing and profiling transcriptomes.RESUMENEn los últimos años, la técnica RNA-Seq  ha tenido un desarrollo acelerado y se ha convertido en el método de elección para el estudio y la caracterización de los transcriptomas dinámicos, aprovechando las tecnologías de secuenciación de alto rendimiento. Estudios aplicando RNA-Seq han mostrado la magnitud, noción y complejidad del transcripotma. A partir de 2008, año de introducción de la técnica, los estudios con RNA-Seq se han multiplicados por más de 2822 veces sólo en 6 años. Al compararse con otros métodos, los estudios empleando RNA-Seq contribuyen a una estimación más precisa de la expresión génica y de las isoformas de los transcriptos. Además, algunas de las aplicaciones potenciales de RNA-Seq no se pueden llevar a cabo con otros métodos. El uso de RNA-Seq aumenta la velocidad de obtención de información y disminuye los costos, logrando con su uso, que investigaciones diversas se vuelvan más frecuentes y precisas. RNA-Seq es un método interdisciplinario que interconecta la biología a otros temas científicos. En este artículo se describe el planteamiento de la tecnología RNA-Seq, metodologías y los métodos realizados en la caracterización de transcriptomas.